Pemandu Wisata Inovasi Aplikasi Pariwisata Cerdas Untuk Penyewaan Layanan Pemandu Wisata Di Lembang - Hariman, Irman (Jurnal Teknologi Informasi, 2024)
This research aims to overcome challenges in the Indonesian tourism industry, which in fact faces classic problems such as lack of accessibility of information and references by developing a smart tourism application that supports integration with the smart city vision. With a qualitative approach and Extreme Programming (XP) methodology, research shows that integration of tour guide service preferences with other services is the main key. Therefore, the "Smart Tourism" system is proposed as a solution, which integrates various travel services into one complete application, providing a one-stop solution holiday service. The research results show that this application makes it easier for tourists to order tour guide services and other services, while providing a variety of preferences that can be personalized by the user and is supported by a decision support system (DSS) based on collaborative user filtering which improves the user experience. Keywords: tourism, smart city, smart tourism, ordering tour guide services.